The Possibilities and Importance of Assessing the Left Atrioventricular Coupling Index Using Various Diagnostic Imaging Methods in an Adult Population: A Comprehensive Review - Małgorzata Poręba; Krzysztof Kraik; Igor Zasoński; Oskar Ratajczyk; Łukasz Paździerz; Angelika Chachaj; Rafał Poręba; Paweł Gać (Journal of Cardiovascular Development and Disease)
Cardiovascular diseases are a leading cause of death worldwide, and they are becoming even more frequent due to the aging of society. Due to this fact, new parameters that are useful in diagnosing, as well as in assessing, the risk of cardiovascular events, and in future prognosis estimation, should be developed. The left atrioventricular coupling index (LACI) has been recently introduced as the one parameter meeting these criteria. The current review aims to collect all available data and assess whether the LACI may be a valuable tool in daily clinical practice, and, simultaneously, to direct future research on the subject. The LACI is a parameter that can be calculated based on echocardiographic, cardiac CT and CMR examinations. It appears to be of use in several cardiovascular diseases, especially heart failure and atrial fibrillation, both in diagnostics and as a prognostic marker. Moreover, the LACI is a useful marker in cardiomyopathies, myocardial infarction, beta-thalassemia major and light-chain amyloidosis. However, the number of studies on the subject of LACI is limited, and some of these studies are based on the same cohort of patients. Future studies should take up the subject of the LACI, especially when it comes to the value of calculating the LACI based on various imaging techniques, including echocardiography.